Welfare impacts of some limitation on trawler catches and fishing effort in the Gulf of Thailand - Janekarnkij, Penporn (1986)
The over all objective of the study is to examine the net welfare effects of an imposition of some fishing regulations on trawlers in the Gulf of Thailand. The factors affecting supply of and demand for trawler catches, such as, trash fish and other catches are also examined. The income effects of change in the price of commodity was assumed to be zero. The change in consumer surplus and producer surplus were used as the measurements of change in net social welfare. It is assumed that a unit gain or loss in producer surplus is equal to a unit gainor loss in consumer surpluse from trawler fishery after the imposition of regulation son trawler catches and fishing efforts were evaluated. Ordinary least squares (OLS),twos tageleast squares (2SLS) , and first order auto regressive techniques CARl) were used to test the empiral results.Monthly data (1979-1982) on trawelatches and trawling efforts in the Gulf of Thailand, prices of trawler catches and fish meal,and price index of meats other than sea foods are used for the analysis.